(4+3i)(5+5i)=0

Simple and best practice solution for (4+3i)(5+5i)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4+3i)(5+5i)=0 equation:


Simplifying
(4 + 3i)(5 + 5i) = 0

Multiply (4 + 3i) * (5 + 5i)
(4(5 + 5i) + 3i * (5 + 5i)) = 0
((5 * 4 + 5i * 4) + 3i * (5 + 5i)) = 0
((20 + 20i) + 3i * (5 + 5i)) = 0
(20 + 20i + (5 * 3i + 5i * 3i)) = 0
(20 + 20i + (15i + 15i2)) = 0

Combine like terms: 20i + 15i = 35i
(20 + 35i + 15i2) = 0

Solving
20 + 35i + 15i2 = 0

Solving for variable 'i'.

Factor out the Greatest Common Factor (GCF), '5'.
5(4 + 7i + 3i2) = 0

Factor a trinomial.
5((4 + 3i)(1 + i)) = 0

Ignore the factor 5.

Subproblem 1

Set the factor '(4 + 3i)' equal to zero and attempt to solve: Simplifying 4 + 3i = 0 Solving 4 + 3i = 0 Move all terms containing i to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3i = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 3i = 0 + -4 3i = 0 + -4 Combine like terms: 0 + -4 = -4 3i = -4 Divide each side by '3'. i = -1.333333333 Simplifying i = -1.333333333

Subproblem 2

Set the factor '(1 + i)' equal to zero and attempt to solve: Simplifying 1 + i = 0 Solving 1 + i = 0 Move all terms containing i to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + i = 0 + -1 Combine like terms: 1 + -1 = 0 0 + i = 0 + -1 i = 0 + -1 Combine like terms: 0 + -1 = -1 i = -1 Simplifying i = -1

Solution

i = {-1.333333333, -1}

See similar equations:

| 0.7x=43 | | 3x+11+7x+9=180 | | 112-(7x+11)=7(x+8)+x | | 4(5.5x+1.5)+-4.5(8x+4)= | | 2x+9+3x+x=5x+7 | | 2x+9+3x+x=5x+8 | | 4r+5=29 | | 12(9)+8(9)= | | 4(5.5x+1.5)-4.5(8x+4)= | | 13=y-14 | | 64x^2-176x+121=0 | | 1-1.5v=.04-.3v | | (4t)(7)(5)= | | 53+(x-11)=180 | | 722-11x=55x | | (6.65+5c)-(4.15+4c)= | | (6.65+5c)-(4.15+4c)= | | (6.65+5c)-(4.15+4c)= | | (6.65+5c)-(4.15+4c)= | | (6.65+5c)-(4.15+4c)= | | 6x+x=90 | | (6.65+5c)-(4.15+4c)= | | 53+x-11=180 | | -20x=44-8y | | 12x+2y=54 | | 5=u+5 | | -12z-6=-6(2x+1) | | .25t+7.5=14 | | 8y-9=5 | | 105+9.50x=14.75+9.50x | | 2+3x-x=4(2x-1) | | 2(x+3)-5(2x+1)=5 |

Equations solver categories